An in vivo microdialysis study on the differences of evoked responses in the rat globus pallidus - del Fierro, Ramon S. (Animo Repository, 2004)
This study demonstrates the application of in vivo microdialysis coupled with high performance liquid chromatography and electrochemical detection to the quantification of extracellular levels of the neurotransmitters: dopamine (DA) and serotonin (5-HT); and their acidic metabolites 3,4-dihydroxyphenylaceticacid(DOPAC), homovanillicacid(HVA) and 5-hydroxyindoleacetic(5-HIAA) acid in the rat brain. Specifically, this technique was used to measure levels of these neurotransmitters/metabolites in the Globus pallidus, after perfusion with normal Ringer's solution, and after perfusion with Ringer's solution containing high potassium (100 mM) or tyramine (50 uM). Basal concentration of (5-HT) is higher compared with DA, and concomittantly, there is a higher concentration of the metabolite 5-HIAA. Upon exposure to high potassium, there is an increase in measured levels of 5-HT while decreases in extracellular levels of DOPAC, HVA and 5-HIAA were observed. Upon repolarisation, extracellular levels of DOPAC and HVA increased several-fold before returning to basal levels. By contrast, no corresponding overshoot of 5-HIAA was observed. Following exposure to tyramine, higher DA, DOPAC and HVA levels were detected. This study shows clear differences in basal and evoked releases of DA, 5-HT, DOPAC, HVA and 5-HIAA in the rat Globus pallidus, in vivo. The heterogeneity in release profiles may be attributed to the nature and origins of dopaminergic and serotonergic innervations, activities of catabolic enzymes (specifically monoamine oxidase), efficiencies of neuronal uptake mechanisms, and/or distribution of specific transporters that carry neurotransmitters/metabolites to the extracellular space.